2013
DOI: 10.1175/jcli-d-12-00038.1
|View full text |Cite
|
Sign up to set email alerts
|

Upper Oceanic Energy Response to Tropical Cyclone Passage

Abstract: The upper oceanic temporal response to tropical cyclone (TC) passage is investigated using a 6-yr daily record of data-driven analyses of two measures of upper ocean energy content based on the U.S. Navy's Coupled Ocean Data Assimilation System and TC best-track records. Composite analyses of these data at points along the TC track are used to investigate the type, magnitude, and persistence of upper ocean response to TC passage, and to infer relationships between routinely available TC information and the upp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 47 publications
0
37
0
Order By: Relevance
“…Note, the SST represents a lower boundary condition in HURMOD. Hence the ocean is considered as an unlimited energy reservoir, whereas the airÁsea interaction associated with real TCs results in a cooling of surface waters beneath the TC due to enhanced vertical turbulent entropy fluxes into the atmosphere, vertical turbulent mixing within the ocean mixed layer and upwelling (Knaff et al, 2013;Mei and Pasquero, 2013). In case I, we also run simulations with different values for the tropopause temperature to test the sensitivity to vertical temperature stratification and outflow temperature.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Note, the SST represents a lower boundary condition in HURMOD. Hence the ocean is considered as an unlimited energy reservoir, whereas the airÁsea interaction associated with real TCs results in a cooling of surface waters beneath the TC due to enhanced vertical turbulent entropy fluxes into the atmosphere, vertical turbulent mixing within the ocean mixed layer and upwelling (Knaff et al, 2013;Mei and Pasquero, 2013). In case I, we also run simulations with different values for the tropopause temperature to test the sensitivity to vertical temperature stratification and outflow temperature.…”
Section: Experimental Set-upmentioning
confidence: 99%
“…Between 16 and 19 September, the storm motion decreased from 5.6 to 3.2 m s 21 , suggesting the potential for increased impact of storm-induced cooling of the underlying ocean. Observationally, Brand (1971), Price (1981), Lin et al (2009), Dare and McBride (2011), and Knaff et al (2013) have shown that slower storm motions tend to produce greater reductions in SST. Simulations by Khain and Ginis (1991), Bender et al (1993), and Bender and Ginis (2000) have yielded similar results and have shown that such cooling can have a significant impact in reducing storm intensity.…”
Section: Weakening Phasementioning
confidence: 99%
“…All six OHC parameters are being used for investigation of potential intensity and they will also be considered as potential input for LGEM. Knaff et al (2012) investigated a number of questions about ocean responses to TCs using the NCODA based OHC26C and T100M in conjunction with the historical TC records. The investigation focused on composite analyses that show the type, magnitude, and persistence of upper ocean response to TC passage as a function of initial ocean conditions, latitude, translation speed, intensity, and a simplified (from TC wind radii) Kinetic Energy (KE) and then discussed possible relationships between these factors and the upper ocean response.…”
Section: Resultsmentioning
confidence: 99%